Lenalidomide in combination or alone as maintenance therapy following autologous stem cell transplant in patients with multiple myeloma: a review of options for and against. (12th December 2017) - Richardson, Paul G.; Holstein, Sarah A.; Schlossman, Robert L.; Anderson, Kenneth C.; Attal, Michel; McCarthy, Philip L.
ABSTRACT: Introduction : Lenalidomide has multifaceted antimyeloma properties, including direct tumoricidal and immunomodulatory effects. Several randomized controlled trials have demonstrated improved patient outcomes with lenalidomide maintenance after autologous stem cell transplant (ASCT) in patients with newly diagnosed multiple myeloma (NDMM). Currently, single-agent lenalidomide is the only approved post-ASCT maintenance therapy in the United States and European Union for patients with NDMM. Areas covered : This review article summarizes the efficacy and safety data of lenalidomide maintenance, as monotherapy and in combination with other agents, following ASCT in patients with NDMM. In addition, emerging therapies with newer agents in this setting are discussed. Expert opinion : Following ASCT, maintenance therapy with lenalidomide until progressive disease is an effective and well-tolerated regimen and represents the standard of care for patients with NDMM. Studies evaluating maintenance with lenalidomide in combination with next-generation proteasome inhibitors, monoclonal antibodies, and histone deacetylase inhibitors may further improve patient outcomes.